2022
DOI: 10.1017/s1755773922000066
|View full text |Cite
|
Sign up to set email alerts
|

Ideological extremism, perceived party system polarization, and support for democracy

Abstract: Does ideological polarization undermine or strengthen people’s principled support for democracy? In this study, we suggest that different manifestations of ideological polarization have different implications in this respect. Using data from 11 surveys conducted with representative samples of the adult populations of a group of liberal democratic countries, part of the Comparative National Elections Project, we look at how people’s level of ideological extremism and their perceptions of ideological polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 87 publications
0
17
1
Order By: Relevance
“…Perceived ideological polarization is understood as the extent to which individuals perceive differences between political opponents' ideological positions and policy preferences (Torcal and Magalhães 2022). The concept concerns the observed dispersion of parties along an ideological continuum, which indicates the set of ideological choices that the parties represent to a voter (Dalton 2008b).…”
Section: Perceived Ideological Polarization: Raising the Utilitarian ...mentioning
confidence: 99%
“…Perceived ideological polarization is understood as the extent to which individuals perceive differences between political opponents' ideological positions and policy preferences (Torcal and Magalhães 2022). The concept concerns the observed dispersion of parties along an ideological continuum, which indicates the set of ideological choices that the parties represent to a voter (Dalton 2008b).…”
Section: Perceived Ideological Polarization: Raising the Utilitarian ...mentioning
confidence: 99%
“…In Colombia, the main leftist party was Polo Democrático (M = 3.51) and the most important party on the right was Partido de la U. Two criteria were used to establish the largest left and For perceived political polarization we used a measure that has been widely employed in the past in multinational studies (see, for example, Singer, 2016;Torcal & Magalhães, 2022;Yang et al, 2016). This measure is detailed in the literature review prepared by Tucker et al (2018, p. 8).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Affective polarization can be a relevant indicator of how well the democratic system works. When affective polarization is high, the possibility of reaching agreements is hampered by the way in which conflicts between groups are faced and solved (Iyengar et al, 2012;Torcal and Comellas, 2022;Torcal and Magalhaes, 2022). Research has shown that higher levels of affective polarization have effects in the political arena (Druckman et al, 2020(Druckman et al, , 2021Kingzette et al, 2021;Rodon, 2022;Serani, 2022;Torcal and Carty, 2022), but also in other areas (Iyengar and Westwood, 2015;Iyengar et al, 2019;Rudolph and Hetherington, 2021).…”
Section: A Ective Polarization In Low Partisanship Societiesmentioning
confidence: 99%